The role of technologies, finance, and green energies in transforming Middle East and North African environmental sustainability - Lanouar Charfeddine; Montassar Kahia; Abdul Rahman (Sustainable Futures)
This paper contributes to the empirical literature on environmentally sustainable policies. To this end, the study explores the crucial role of information and communication technologies (ICT), foreign direct investment (FDI), and renewable energy intensity (REI) in enhancing environmental quality in the Middle East and North African (MENA) region. This paper extends the STIRPAT model by incorporating three variables of interest namely ICT, FDI, and REI. The proposed framework is empirically tested using a panel VAR model for a sample of 13 selected MENA countries from 1995 to 2018. The empirical findings indicate that ICT reduces the level of CO2 emissions, while its effects on the ecological footprint provide mixed results. Moreover, the outcomes further confirm that FDI degrades the environmental quality of the region. However, relatively a more pronounced impact was found for oil-exporting economies compared to oil-importing economies. On the other hand, the impact of REI on environmental degradation is found mixed. The analysis, based on impulse response functions, variance decomposition, and causality analysis, provides strong evidence for the importance of these factors in explaining environmental degradation. Several tailored policies have been proposed and discussed for transforming environmental sustainability in the MENA region.